A Systematic Review of Literature of Future Trends of AI and VR in HRM - Agrawal, Kriti; Sunil (International Journal of Social Sciences and Management, 2025)
Human Resource Management is constantly transforming itself in the context of organizational productivity. This transformation is heavily impacted in the presence of metaverse, virtual reality and internet of things. This review is conducted addressing two objectives: 1) To identify the main themes that have an impact on managing learning in organizations and (2) To identify innovative work behaviors that are developing gradually as a result of introduction of artificial intelligence and virtual reality. The systematic literature review (SLR) approach served as the foundation for this article's positioning as a literature review. The review comprised seventy-four papers from the Science Direct databases that were published between 1985 and 2025. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) served as the foundation for the screening, inclusion, analysis, and reporting of the findings of the articles. In addressing the first objective, it was found that learning in organizations is impacted by adoption of virtual reality resulting in many organizational and employee centric outcomes. The outcomes include insights into the multifaceted role of artificial intelligence encompassing candidate screening, personalized training, engagement enhancement, and performance assessment. A conceptual framework was created based on the gaps found about the factors that influence innovative work behaviors and their beneficial effects in order to address the study's second goal. The viewpoints were inferred from theoretical justifications and review findings. The results pertaining to the two goals have both theoretical and practical ramifications. One important practical implication is that managers' and employees' action and work-based learning may recommend implementing disruptive technology for HRM, which causes firms to reconsider HR procedures and tactics. As a result, traditional methods have become outdated. Additionally, the results offer some additional avenues for future study. The study found empirically proven determinants of innovative work behaviors which also results in a new form of leadership. These were synthesized based on the studies conducted during the period 1985-2025. This synthesis and theoretical grounding deduced a conceptual framework for determining the outcomes of disruptive technologies for HRM. Int. J. Soc. Sc. Manage. Vol. 12, Issue-4: 158-168.